Análise dos efeitos do tratamento de ozonização de fluidos de corte solúveis em um processo de fresamento - Santos, Fabio de Sousa (2016)
The disposal of degraded cutting fluid is an additional cost to machining processes, but has also damaged to the environment. To reduce machining costs some researchers are using techniques to treat cutting fluids during the machining, ensuring a longer product life and minimizing disposal volumes. This work, through an electrophysical catalyst, verified the effects of treatment process for ozonation, for either a fluid of vegetable based Jatropha (Jatrophacurcas) as for a product of semisynthetic mineral base ROCOL ULTRACUT 360 °, in a milling process using nodular cast iron GGG60 as raw material. To it were evaluated the mechanical charactheristics on during the milling process and the physicochemical characteristics of the cutting fluid. The results in new fluid composition to the treated fluid is the fluid treated in relation to the mechanical characteristics such as tool wear, surface roughness and hardness of the specimens were constant for the new fluid, while there was an improvement in consumption cutting power for milling and a worsening in the oxidation of workpiece. The physicochemical characteristics of cutting fluids, the pH could be restored while the dissolved oxygen no significant change and the elimination of microorganisms did not get the expected result.